Implementation of Chest Physiotherapy and Eucalyptus Aromatherapy On Oxygen Saturation and Airway Cleaning: Case Study - Afifah Afdiani Qurrokhmah; Eni Rahmawati (International Journal of Biomedical Nursing Review, 2023)
Introduction: Pneumonia is a respiratory tract infection that attacks the lungs and usually affects children under five years of age. Management of children with pneumonia is one of them with supporting treatment. Purpose: Determine the effect of chest physiotherapy and eucalyptus aromatherapy on increasing oxygen saturation and airway clearance in pediatric patients with pneumonia. Results: An increase in oxygen saturation was already visible during the first intervention and airway clearance increased after the intervention was carried out on the second day. Conclusion: There is an increase in oxygen saturation and respiratory clearance after being given chest physiotherapy intervention and eucalyptus aromatherapy.